Extreme morning chronotypes are often familial and not exceedingly rare: the estimated prevalence of advanced sleep phase, familial advanced sleep phase, and advanced sleep–wake phase disorder in a sleep clinic population. Issue 10 (6th August 2019) - Curtis, Brian John; Ashbrook, Liza H; Young, Terry; Finn, Laurel A; Fu, Ying-Hui; Ptáček, Louis J; Jones, Christopher R
Abstract: Study Objectives: Report the first prevalence estimates of advanced sleep phase (ASP), familial advanced sleep phase (FASP), and advanced sleep–wake phase disorder (ASWPD). This can guide clinicians on the utility of screening for extreme chronotypes both for clinical decision-making and to flag prospective participants in the study of the genetics and biology of FASP. Methods: Data on morning or evening sleep schedule preference (chronotype) were collected from 2422 new patients presenting to a North American sleep center over 9.8 years. FASP was determined using a severity criterion that has previously identified dominant circadian mutations in humans. All patients were personally seen and evaluated by one of the authors (C.R.J.). Results: Our results demonstrate an ASP prevalence of 0.33%, an FASP prevalence of 0.21%, and an ASWPD prevalence of at least 0.04%. Most cases of young-onset ASP were familial. Conclusions: Among patients presenting to a sleep clinic, conservatively 1 out of every 300 patients will have ASP, 1 out of every 475 will have FASP, and 1 out of every 2500 will have ASWPD. This supports obtaining a routine circadian history and, for those with extreme chronotypes, obtaining a family history of circadian preference. This can optimize treatment for evening sleepiness and early morning awakening and lead to additional circadian gene discovery. We hope these findings will lead to improved treatment options for a wide range of sleep and medical disorders in the future.